Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content: 1. Instructional Design in Calculus Based on Realistic Mathematics Education Approach (RME) and its Effectiveness on Problem solving skills among high school students Instructor. Faisal Ali Saleh Alssenai, Prof. Abullah Abbas Mahdi, Co-Prof. Dhikra Mohammad Al-Baqeri 2. The Effectiveness of an interactive electronic book in a Unit in The Science course in Developing Visual Thinking Skills and the Enjoyment of Learning Science among fourth grade students Dr. Eman Saber Abdelkader Elazzab, Mrs. Ebtsam Ayied M. Elqahtany 3. The effectiveness of using Tellagami software to raise awareness of the Omani historical effects of eleventh graders Mrs. Zouwaina Khalaf Mahfood Al-Ghawi, Dr. Hamad Suleiman Salem Al-Salmi 4. The effect of difference type of electronic discussion on the achievement for secondary school students in Jeddah Mr. Tariq Ali Al-Malki, Mr. Ali Mohammad Al-Shehri 5. The Effectiveness of Internet of Things Applications in a Personal Learning Environment in Developing Cognitive Achievement in Programming Skills for the Intermediate School Students in Rabigh Governorate Mrs. Manahi Saleh Altayari, Prof. Najwa Atayan Almohammadi 6. The effectiveness of a program based on multiple intelligences in developing the creative expression skills of outstanding students at the secondary level in Sana’a, the capital, Sana’a Mr. Mohammed Abdu-Allah Almnswory 7. Educational Research Orientations in the field of Curricula and Teaching Methods of English Language in Arab World during the Period 2020-2022 Mrs. Fawzeyah Khafeer Al-Khathami, Prof. Hanan Ahmad Al-Saeedi